Handbook of cathodic corrosion protection : theory and practice of electrochemical protection processes - Baeckmann, W. von; Schwenk, W.; Prinz, W.; Baeckmann, W. von (Gulf Pub. Co., 1997)
This comprehensive handbook covers all aspects of cathodic protection in terms of both practice and theory.